PEG/PEI-functionalized single-walled carbon nanotubes as delivery carriers for doxorubicin: synthesis, characterization, and in vitro evaluation - Yang, Shuoye; Wang, Zhenwei; Ping, Yahong; Miao, Yuying; Xiao, Yongmei; Qu, Lingbo; Zhang, Lu; Hu, Yuansen; Wang, Jinshui (Beilstein Journal of Nanotechnology, 2020)
Single-walled carbon nanotubes (SWCNTs) have attracted great interest regarding drug-delivery applications. However, their application has been limited by some inherent disadvantages. In this study, raw SWCNTs were purified with different oxidizing acids, and the resulting shortened CNTs were conjugated with poly(ethylene glycol) (PEG) and polyethylenimine (PEI). The different nanocarriers, that is, CNTs-COOH (CNTs), CNTs-PEG and CNTs-PEG-PEI, were systematically characterized and evaluated in terms of drug loading, in vitro release, cytotoxicity towards MCF-7 cells and cellular uptake. The results showed that all CNT carriers had a high drug loading capacity. In comparison with CNTs-COOH and CNTs-PEG, CNTs-PEG-PEI showed a more rapid drug release under acidic conditions and a higher antitumor activity. Furthermore, fluorescence detection and flow cytometry (FCM) analysis results indicated that the internalization into cells of CNTs-PEG-PEI was significantly enhanced, thus inducing tumor cell death through apoptosis more efficiently. The above series of benefits of CNTs-PEG-PEI may be attributed to their good dispersibility and comparably higher affinity to tumor cells due to the difunctionalization. In summary, the PEG- and PEI-conjugated CNTs may be used as novel nanocarriers and the findings will contribute to the rational design of multifunctional delivery vehicles for anticancer drugs.
Keywords: antitumor activity; cellular uptake; PEG functionalization; PEI functionalization; poly(ethylene glycol) (PEG); polyethylenimine (PEI); single-walled carbon nanotubes